INTERCONNECTIONS BETWEEN INTERCULTURALITY, ETHNIC DIVERSITY AND HUMAN RIGHTS IN SOCIAL TRANSFORMATION: A STUDY ON NATIVE PEOPLES AND TRADITIONAL COMMUNITIES IN THE LIGHT OF THE FEDERAL CONSTITUTION OF 1988 - Penna, Maria Cristina Vitoriano Martines; Guedes, Marcio Bulgarelli; Guedes, Laise Reis Silva; Ramos, Paula Gabriela Coetti (Seven Editora, 2025)
This article addresses the interconnection between interculturality, ethnic diversity and human rights in social transformation, with emphasis on Native Peoples and Traditional Communities with the advances of the Federal Constitution of 1988, using a qualitative, doctrinal and bibliographic methodology explores the relationship between interculturality, ethnic diversity and human rights in the context of social transformation in Brazil, with a focus on indigenous peoples and traditional communities. The study highlights the importance of interaction between different cultures for the recognition and appreciation of ethnic diversity, which is fundamental for guaranteeing the human rights of these groups. The analysis is based on the 1988 Constitution, which is considered a significant legal framework for the affirmation of the rights of indigenous peoples and traditional communities. The text discusses how interculturality and ethnic diversity are crucial for social transformation. This includes the struggle for recognition of rights, preservation of cultures and territories, and active participation in society. The 1988 Constitution is seen as a key instrument for this transformation, as it recognizes the interculturality of Brazil and ensures fundamental rights to these groups. DOI: https://doi.org/10.56238/sevened2024.037-191